Peningkatan Harmonisasi Paduan Suara Universitas Tarumanagara Melalui Komunikasi Nonverbal Konduktor - Cita Marito Sitorus; Ahmad Junaidi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The success of a choir performance is critically dependent on the synergy achieved through the conductor's nonverbal communication. This research aims to deeply analyze the nonverbal communication strategies used by the conductor of the Universitas Tarumanagara Choir (PSUT), Jason Ferdison, to enhance harmonization, musical unity, and overall performance quality. Using a Qualitative Descriptive approach with a Case Study design on PSUT, the study focuses on three key nonverbal strategies derived from Green's (2019) model: Gestural Clarity Strategy, Emotional Expressiveness Strategy, and Interpersonal Regulation Strategy. Data were collected through in-depth interviews with the conductor and four key singers, passive non-participant observation, and documentation. Data analysis employed the interactive model of Miles, Huberman, and Saldana (2018). Findings reveal that the conductor consciously applies these strategies: Gestural Clarity (using clear Ictus and the Axis XYZ system for dynamics) secures technical unison; Emotional Expressiveness (facial and bodily) creates emotional unison in interpretation, aligning with Ekman's theory; and Interpersonal Regulation (Oculesics/eye contact) acts as a supportive nonverbal correction tool, reflecting transformational leadership. The high level of harmonization achieved, particularly during complex pianissimo sections, proves the efficacy of these nonverbal cues. However, a gap exists in the interpretation of complex, spontaneous gestures due to lack of singer focus, highlighting the crucial role of chemistry and repeated rehearsal exposure in bridging this nonverbal gap. Keberhasilan penampilan paduan suara sangat bergantung pada sinergi yang dicapai melalui komunikasi nonverbal konduktor. Penelitian ini bertujuan mengkaji secara mendalam strategi komunikasi nonverbal yang diterapkan konduktor Paduan Suara Universitas Tarumanagara (PSUT) untuk meningkatkan harmonisasi, kesatuan musikal, dan kualitas penampilan. Kajian ini berfokus pada tiga strategi nonverbal utama: Klarifikasi Gestur, Ekspresi Emosional, dan Regulasi Interpersonal. Pendekatan Deskriptif Kualitatif dengan desain Studi Kasus pada PSUT, data dikumpulkan melalui wawancara mendalam dengan konduktor kunci dan informan pendukung (penyanyi), observasi partisipan pasif selama latihan, dan dokumentasi. Analisis data menggunakan model interaktif Miles, Huberman, dan Saldana (Kondensasi, Penyajian, dan Penarikan Kesimpulan). Kerangka teoritis dibangun di atas Teori Komunikasi Nonverbal (Kinesics, Oculesics, Proxemics), Komunikasi Organisasi, dan Strategi Komunikasi, khususnya strategi nonverbal Klarifikasi, Ekspresi Emosional, dan Regulasi Interpersonal. Temuan awal menunjukkan bahwa penggunaan klarifikasi gestur yang presisi menghilangkan ambiguitas, sementara ekspresi emosional memandu interpretasi musikal yang lebih mendalam (unison). Regulasi interpersonal melalui kontak mata dan postur membangun kepercayaan diri dan motivasi, yang penting untuk mencapai balance dan blend optimal. Penelitian ini krusial untuk memberikan panduan praktis bagi konduktor dan memperkaya literatur tentang interaksi antara isyarat nonverbal dan kinerja musik.